An Analysis of African American Vernacular English Grammatical Features in Shark Tale Film - Pamangin, Ronnaoranska Rombe; Arifin, M Bahri; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
Every language varies and has its own characteristics. The varieties can be seen in terms of age, gender, region, social class, ethnicity, etc. One of the characteristics of a language is its grammatical features. An example of language variety that is affected by ethnic group is African American Vernacular English (AAVE). This research aimed to analyze the grammatical features of AAVE through Oscar’s utterances in Shark Tale film and the variables that influence his AAVE utterances by using Wolfram and Rickford & Rickford’s Theory. Out of four AAVE grammatical features, the researcher found that Oscar produced three of them which are verb phrase, negation, and nominal. Question formation feature is not found in Oscar’s utterances. AAVE grammatical features that appeared in Oscar’s utterances are copula/auxiliary absence, habitual be, double modals, subject-verb-agreement, ain’t, multiple negation, plural noun suffix–s deletion, and y’all. Those grammatical features are influenced by his lower working-class status, his male gender, his young age, and his mood which the AAVE utterances produced whether he was comfortable or uncomfortable with the audiences or with the topic.